Trade liberalization and the quest for peace and prosperity: The fate of an idea in the minds of Woodrow Wilson and Cordell Hull - Nevins, Bernard L (University of Ottawa (Canada), 1977)
Abstract not available.
Keywords: History, United States.; Political Science, International Relations.